Ilmu dan Teori-Teori Kebenaran, dan Kontekstualisasinya dengan Pendidikan Islam - Koto, Eldawati; Wahab, Muhbib Abdul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this academic writing, there are three main discussions. The first discussion is about whether knowledge comes solely from reason ('aqliyyah). Next, the second discussion focuses on whether the